2019
DOI: 10.1002/fsn3.948
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of different drying methods on the phenolic compounds, antioxidant activity, and in vitro digestion of green coffee beans

Abstract: We investigated the effects of different drying methods (room temperature drying, heat pump drying, freeze drying, microwave vacuum drying [MVD], and combined microwave power vacuum drying) on the active ingredients of green coffee beans. We specifically focused on eleven phenolic acids, total phenolic content (TPC), total flavonoid content, antioxidant activity, polyphenol oxidase (PPO), the inhibition of linoleic acid peroxidation (LPO), and enzyme activity, and the bio‐accessibility in vitro and bioavailabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 44 publications
5
28
0
Order By: Relevance
“…And the highest flavonoid content was found in IRD samples, approximately 1.60 times higher than that of FVD. It was supported by Cheng et al (2019), who also found that FVD resulted in less phenolic and flavonoid contents of green coffee beans compared with MVD and HAD, which was consistent with our results. Heating created more destruction of the tissue, which in turn led to the thermal degradation or transformation into simpler phenolic compounds, and polymerization or oxidation of phenolic and flavonoid compounds (Si et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…And the highest flavonoid content was found in IRD samples, approximately 1.60 times higher than that of FVD. It was supported by Cheng et al (2019), who also found that FVD resulted in less phenolic and flavonoid contents of green coffee beans compared with MVD and HAD, which was consistent with our results. Heating created more destruction of the tissue, which in turn led to the thermal degradation or transformation into simpler phenolic compounds, and polymerization or oxidation of phenolic and flavonoid compounds (Si et al, 2016).…”
Section: Resultssupporting
confidence: 93%
“…The comparison of means between different treatments is shown in Also, following the FD method, the TFC in the HA-MW dryer was higher than other dryers (HA-IR, MW, IR, HA, and SD), because the moderate heat (resulting from the MW power and air temperature at the same time) leads to the swelling of raw materials, softening and acceleration of the rupture of plant tissue, decomposition of cellular components and thus, facilitating the extraction of flavonoids (Cheng et al, 2019;Kubra et al, 2015). This result is consistent with the results of and Li et al (2019).…”
Section: Total Flavonoid Contentmentioning
confidence: 94%
“…The use of FD is not limited to fruits and vegetables; it has been used to produce dried specialty foods from plant sources such as coffee, tea, and spices [4,7,8,11,[58][59][60][61][62][63][64][65].…”
Section: Speciality Foodsmentioning
confidence: 99%
“…Kraujalyte et al [62] found that instant tea produced by FD had high concentration of volatile compounds (318.65 ng/g), which was comparatively two to five times higher than those produced by other drying methods (68.60 to 143.33 ng/g). In the case of coffee, the content of phenolic acids in coffee beans after FD was reported to increase by 41% more than in fresh green coffee beans [59]. A FD process for coffee has been recently designed using mathematical modeling to optimize energy efficiency and preserve the important flavors and nutrients [9].…”
Section: Speciality Foodsmentioning
confidence: 99%